Sugar codes conjugated alginate: an innovative platform to make a strategic breakthrough in simultaneous prophylaxis of GERD and "Helicobacter pylori" infection - Moayedi, Saeed; Yadegar, Abbas; Balalaie, Saeed; Yarmohammadi, Mahdiyeh; Zali, Mohammad Reza; Suzuki, Hidekazu; Fricker, Gert; Haririan, Ismaeil (Drug design, development and therapy, 2020)
Sugar Codes Conjugated Alginate: An Innovative Platform to Make a Strategic Breakthrough in Simultaneous Prophylaxis of GERD and Helicobacter pylori Infection